Spontanschreibung im Chat - Burri, Gabriela (Linguistik Online, 2003)
In this article spontaneous writing in chat communication is analyzed in two aspects. On one hand, the spelling forms found here show some language change tendencies in the German spoken language. On the other hand, the article tries to describe on which writing conventions these spontaneous spellings are based.